Maps, Movement, and Meaning: Children Restorying Thresholds with Heart Maps and Walking Tours as Acts of Spatial Reclamation - Casey M. Pennington (Education Sciences)
This qualitative study examines how children living in a public housing neighborhood engage in multimodal, embodied meaning-making to restory their community. Focusing on two participants and in partnership with The Kids Club, this paper explores children’s spatial reclamation through embodied and spatialized literacies, complicating stories where children assert whose stories matter and why. Drawing on nexus analysis and narrative inquiry, this study conceptualizes the body as central to cognition and comprehension through texts in action. The sisters spatially reclaim neighborhood narratives via walking tours, heart maps, and photographs that function as multimodal action texts. These practices invite a rethinking of comprehension beyond traditional textual modes, illuminating how children navigate and transform literacy landscapes. This work contributes to conversations about equity in literacy environments and calls on educators and researchers to honor children’s multimodal literacy practices as vital forms of critical comprehension, storytelling, and belonging.